Taman Siswa: Pemikiran Ki Hajar Dewantara Dalam Tinjauan Historis - Ismaul Fitroh; Moh. Imron Rosidi (Departement of Mathematics Education, 2023)
This study aims to explore the history of the Taman Siswa, the development of Taman Siswa and how the government reacted at that time. This study uses historical research methods with several steps, namely: heuristics, criticism, interpretation and historiography. The research results show that: (1). Taman Siswa was founded by Suwardi Suryaningrat or Ki Hajar Dewantara. Taman Siswa plays a role in fostering a sense of Indonesian nationalism. In its educational process Taman Siswa adheres to three mottoes, namely: Ing Ngarso Sung Tuladha, Ing Madyo Mangun Karso and Tut Wuri Handayani; (2). The development of Taman Siswa began with the formation of Taman Kanak-Kanak, Taman Anak, Taman Muda, Taman Dewasa, Taman Madya, Taman Guru to Taman Masyarakat; (3). The Dutch colonial government’s reaction to the emergence and development of Taman Siswa turned out to be that the colonial government was trying to obstruct the development of Taman Siswa, but Ki Hajar Dewantara was against it. One of the results of Ki Hajar Dewantara’s struggle was that starting in 1938 all civil servants who sent their children to school, both in subsidized public schools and in private schools, had the same right to child support.